2007
DOI: 10.1016/j.neuroimage.2007.05.017
|View full text |Cite
|
Sign up to set email alerts
|

A brief thought can modulate activity in extrastriate visual areas: Top-down effects of refreshing just-seen visual stimuli

Abstract: Current models of executive function hold that the internal representations of stimuli used during reflective thought are maintained in the same posterior cortical regions initially activated during perception, and that activity in such regions is modulated by top-down signals originating in prefrontal cortex. In an event-related functional magnetic resonance imaging study, we presented participants with two pictures simultaneously, a face and a scene, immediately followed either by a repetition of one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
100
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 48 publications
14
100
0
Order By: Relevance
“…4). Furthermore, imaging evidence that levels of neural activity within temporal lobe face processing areas are modulated by top-down signals originating in PFC [16,24,34,58] is consistent with the notion that the frontal lobes exert executive control over the recognition process (Fig. 4).…”
Section: Discussionsupporting
confidence: 78%
“…4). Furthermore, imaging evidence that levels of neural activity within temporal lobe face processing areas are modulated by top-down signals originating in PFC [16,24,34,58] is consistent with the notion that the frontal lobes exert executive control over the recognition process (Fig. 4).…”
Section: Discussionsupporting
confidence: 78%
“…During a memory task, stored representations of relevant information must be recruited during recall (Goodale & Milner, 1992;Klatzky et al, 1993). Additionally, studies have shown that the process of remembering often reactivates sensoryspecific cortices that were first activated during the encoding of stimulus features (Johnson, Mitchell, Raye, D'Esposito, & Johnson, 2007;Geng, Ruff, & Driver, 2009). By directly comparing two conditions for which the contribution of the ventral stream is hypothesized to differ, we have shown that the N170 likely reflects perceptual requirements during mnemonic processing specifically linked to action.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, even the strongest predictions in the current task may result in only moderate activation: There is only a single opportunity to associate C items with their context, predictions were incidental with respect to the categorization task during encoding, and prediction is internally generated activation -such activation is weaker than perceptual activation in general (27). When activation levels fall in this low-to-moderate range, the nonmonotonic plasticity hypothesis posits that the relationship of item activation to memory will be negative: Weak predictions will be neutral, whereas stronger predictions (leading to moderate activation) will induce forgetting.…”
Section: Significancementioning
confidence: 92%
“…To test this idea, we related perception strength-i.e., classifier evidence for the C category in initial triplets-to subsequent memory. We expected that the perception of an item would elicit substantially higher activation levels than its later context-based prediction (27), leading to a positive relationship with subsequent memory.…”
Section: Significancementioning
confidence: 99%